RULES

advertisement
RULES
Arithmetic sequence:
Tn= a+(n-1) d
general term
๐’
Sn= [2a + (n-1) d]
๐Ÿ
๐’
Sn= [a+l]
๐Ÿ
0>a+(n-1) d
when order first negative term.
Geometric sequence:
Tn= arn-1
Sn=
S∞=
general term
๐’‚(๐’“๐’ −๐Ÿ)
๐’“−๐Ÿ
๐’‚
๐Ÿ−๐’“
Matrices & determinists:
๐Ÿ
(
−๐Ÿ
๐Ÿ‘
)
๐Ÿ“
Row
Column
Order= Row × Column 2×2
โ€ซูˆู…ุชุชุบุจุงุด ุฑโ€ฌ
โ€ซูˆุชุถุจ ู‡ู… ู ุจุนุถ ู‡ู…ุง ูƒุฏุง ุดูƒู„ู‡ู… ุญู„ูˆโ€ฌ
1
๐Ÿ
A= (
๐Ÿ
−๐Ÿ‘
)
๐Ÿ•
๐Ÿ ๐Ÿ
- At= (
)
−๐Ÿ‘ ๐Ÿ•
๐Ÿ −๐Ÿ”
- 2A= (
)
๐Ÿ’ ๐Ÿ๐Ÿ’
๐Ÿ
- A2 = A × A = (
๐Ÿ
- (
[(๐Ÿ × ๐Ÿ) + (−๐Ÿ‘ × ๐Ÿ)]
[(๐Ÿ × ๐Ÿ) + (๐Ÿ• × ๐Ÿ)]
๐Ÿ
๐Ÿ“
๐Ÿ
|
๐Ÿ”
๐Ÿ
|๐Ÿ
๐Ÿ“
๐Ÿ
๐Ÿ
๐Ÿ‘
|
−๐Ÿ‘
๐Ÿ
)×(
๐Ÿ•
๐Ÿ
−๐Ÿ‘
) = Row × Column
๐Ÿ•
[(๐Ÿ × −๐Ÿ‘) + (−๐Ÿ‘ × ๐Ÿ•)]
)
[(๐Ÿ × −๐Ÿ‘) + (๐Ÿ• × ๐Ÿ•)]
= [(2×6) -(1×5)] = 12-5 = 7
๐Ÿ•
๐Ÿ
๐Ÿ’| = 2|
๐Ÿ‘
๐ŸŽ
๐Ÿ’
๐Ÿ
| -1 |
๐ŸŽ
๐Ÿ“
๐Ÿ’
๐Ÿ
| +7 |
๐ŸŽ
๐Ÿ“
๐Ÿ
|=
๐Ÿ‘
Using Cramer’s rule to solve it:
- X+2Y=4
๐Ÿ
Δ=|
๐Ÿ
๐Ÿ’
Δx= |
๐Ÿ“
๐Ÿ
Δy = |
๐Ÿ
X=
Y=
๐œŸ๐’™
๐œŸ
๐œŸ๐’š
๐œŸ
=
=
&
2X+Y=5
๐Ÿ
| = (1×1) -(2×3) =-3
๐Ÿ
๐Ÿ
| = (4×1) -(2×5) = -6
๐Ÿ
๐Ÿ’
| = (1×5) -(4×2) = -3
๐Ÿ“
−๐Ÿ”
−๐Ÿ‘
−๐Ÿ‘
−๐Ÿ‘
=2
=1
2
If A= (
๐Ÿ“
๐Ÿ“
๐Ÿ“
Δ=|
๐Ÿ“
๐Ÿ’
) find A-1 (multiplicative inverse of A)
๐Ÿ๐ŸŽ
๐Ÿ’
| = 30
๐Ÿ๐ŸŽ
๐Ÿ
๐Ÿ ๐Ÿ๐ŸŽ
A-1 (
๐œŸ −๐Ÿ“
๐Ÿ ๐Ÿ๐ŸŽ
−๐Ÿ’
)= (
๐Ÿ‘๐ŸŽ −๐Ÿ“
๐Ÿ“
−๐Ÿ
−๐Ÿ’
๐Ÿ‘
) = (−๐Ÿ
๐Ÿ“
๐Ÿ๐Ÿ“
๐Ÿ)
๐Ÿ”
๐Ÿ”
Diffraction:
Y = F(x) ----->
๐’…๐’š
๐’…๐’™
1- If Y = axn -----→
2- If Y= a
3- If Y=
๐Ÿ๐’™๐Ÿ“
5-
6- Y=
๐‘ญ๐Ÿ
๐‘ญ๐Ÿ
๐’…๐’š
=0
๐’…๐’™
----→ Y= 3 (2x-5) ---→
4- F1×F2 ----→
√ ๐’™๐’Ž
= nxaxn-1
๐’…๐’™
a≠0 ----→
๐Ÿ‘
๐’
๐’…๐’š
๐’…๐’š
๐’…๐’š
(F1) × F2 + F1 ×
๐’…๐’™ ๐’…๐’™
๐’…๐’š ๐’Ž
-----→
----→
=
๐’…๐’™
๐’…๐’š
๐’…๐’™
−๐Ÿ๐Ÿ“ -6
x
๐Ÿ
๐’…๐’š
=
๐’Ž
−๐Ÿ
๐’
๐’…๐’™
(F2)
๐‘ฟ
๐’
๐’…๐’š
๐’…๐’š
(๐’‡๐Ÿ )×๐’‡๐Ÿ −๐‘ญ๐Ÿ × (๐’‡๐Ÿ )
= ๐’…๐’™
7- Y= [F(x)] n ------→
๐’…๐’š
๐’…๐’™
๐’…๐’™
(๐‘ญ๐Ÿ )๐Ÿ
= n[F(x)] n-1 ×
๐’…๐’š
๐’…๐’™
F(x)
3
โ€ซโ€ชIntegration:โ€ฌโ€ฌ
โ€ซโ€ช+cโ€ฌโ€ฌ
โ€ซ๐Ÿ‘โ€ฌ
โ€ซโ€ช+cโ€ฌโ€ฌ
โ€ซโ€ช+cโ€ฌโ€ฌ
โ€ซ๐Ÿ‘โ€ช๐Ÿ‘๐’™−โ€ฌโ€ฌ
โ€ซ๐Ÿ‘โ€ช−โ€ฌโ€ฌ
โ€ซ๐Ÿ๐’™โ€ฌ
โ€ซ๐Ÿ‘โ€ฌ
โ€ซ๐Ÿโ€ฌ
โ€ซ๐Ÿโ€ช๐’+โ€ฌโ€ฌ
โ€ซ= โ€ช1- ∫ ๐’‚๐’™ dxโ€ฌโ€ฌ
โ€ซ๐Ÿโ€ฌ
โ€ซ๐Ÿโ€ฌ
โ€ซ= โ€ช2- ∫ √๐’™ dx = ∫ ๐’™ dxโ€ฌโ€ฌ
โ€ซ๐Ÿ‘โ€ฌ
โ€ซ= โ€ช3- ∫ ๐Ÿ’ dx = ∫ ๐Ÿ‘๐’™−๐Ÿ’ dxโ€ฌโ€ฌ
โ€ซ๐’™โ€ฌ
โ€ซโ€ช∫ ๐Ÿ‘ dx = 3x+cโ€ฌโ€ฌ
โ€ซโ€ช4- ∫ ๐’‚ dx = ax+cโ€ฌโ€ฌ
โ€ซโ€ช+cโ€ฌโ€ฌ
โ€ซโ€ช+cโ€ฌโ€ฌ
โ€ซ๐Ÿโ€ช๐’‚๐’™๐’+โ€ฌโ€ฌ
โ€ซ๐’โ€ฌ
โ€ซ๐Ÿโ€ช(๐’‚๐’™+๐’ƒ)๐’+โ€ฌโ€ฌ
โ€ซ๐’‚×)๐Ÿโ€ช(๐’+โ€ฌโ€ฌ
โ€ซ๐Ÿโ€ช[๐‘ญ(๐’™)]๐’+โ€ฌโ€ฌ
โ€ซ๐Ÿโ€ช๐’+โ€ฌโ€ฌ
โ€ซ= โ€ช5- ∫(๐’‚๐’™ + ๐’ƒ)๐’ dxโ€ฌโ€ฌ
โ€ซ๐’š๐’…โ€ฌ
โ€ซ= โ€ช6- ∫[๐‘ญ(๐’™)]๐’ F(x) dxโ€ฌโ€ฌ
โ€ซ๐’™๐’…โ€ฌ
โ€ซโ€ชEx:โ€ฌโ€ฌ
โ€ซ๐’™๐’… ๐Ÿ“)๐Ÿ โ€ช∫ ๐’™(๐Ÿ‘๐’™๐Ÿ −โ€ฌโ€ฌ
โ€ซ๐Ÿโ€ฌ
โ€ซ๐’™๐’… ๐Ÿ“)๐Ÿ โ€ช= ∫ ๐Ÿ”๐’™(๐Ÿ‘๐’™๐Ÿ −โ€ฌโ€ฌ
โ€ซ๐Ÿ”โ€ฌ
โ€ซโ€ช+cโ€ฌโ€ฌ
โ€ซ๐Ÿโ€ฌ
โ€ซ๐Ÿ”]๐Ÿโ€ช[๐Ÿ‘๐’™๐Ÿ −โ€ฌโ€ฌ
โ€ซ๐Ÿ”โ€ฌ
โ€ซ๐Ÿ”โ€ฌ
โ€ซ=โ€ฌ
โ€ซุงู„ุดุฎุต ุงู„ุฐูŠ ู…ูŠูƒู†ู‡ ุฃู† ูŠูƒูˆู† ุฃูŠ ุดุฎุต ูˆูŠุตู†ุน ุฃูŠ ุดูŠุก ุณูˆู ูŠุชุนุฑุถ ู„ู„ู†ู‚ุฏ ูˆุงู„ุฐู… ูˆุฅุณุงุกุฉ ุงู„ูู‡ู…โ€ชุŒโ€ฌโ€ฌ
โ€ซู‡ุฐุง ุฌุฒุก ู…ู† ู…ุซู† ุงู„ุนุธู…ุฉโ€ช.โ€ฌโ€ฌ
โ€ซโ€ช4โ€ฌโ€ฌ
Download